Intra-articular Injection of Mesenchymal Stem Cells After High Tibial Osteotomy: A Systematic Review and Meta-analysis. Issue 11 (23rd November 2022) - Jin, Lingpeng; Yang, Guang; Men, Xiaoqian; Zhang, Jian; Chen, Zhen; Li, Zhongwei; Li, Yusheng; Ma, Jun; Dong, Jiangtao
Background: Multiple studies have investigated the use of mesenchymal stem cells (MSCs) for patients undergoing high tibial osteotomy (HTO), and the effectiveness thereof remains controversial. Purpose: To analyze the effectiveness of intra-articular MSC injection in patients who underwent HTO in terms of clinical outcomes, radiological outcomes, and cartilage repair by a meta-analysis of the available literature. Study Design: Systematic review; Level of evidence, 3. Methods: The electronic databases of PubMed, Embase, Web of Science, and the Cochrane Library were searched from their inception to October 30, 2021, for comparative studies between patients who underwent HTO with and without intra-articular injection of MSCs, according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Study quality was assessed by the Coleman Methodology Score (CMS). Data with comparable results were pooled for meta-analysis. The primary outcomes of interest were the Hospital for Special Surgery (HSS), International Knee Documentation Committee (IKDC), Knee injury and Osteoarthritis Outcome Score (KOOS), and Lysholm scores, as well as the International Cartilage Regeneration & Joint Preservation Society (ICRS) grade of cartilage repair. Radiological outcomes including femorotibial angle, posterior tibial slope, and hip-knee-ankle (HKA) angle were included as secondary outcomes. A fixed-model effect was used for meta-analyses with low heterogeneity between studies ( I 2 < 25%), while the random-model effect was used for medium- to high-heterogeneity analyses ( I 2 ≥ 25%). Results: A total of 843 studies were screened, of which 6 studies with 452 patients met the inclusion criteria and were included. The mean CMS was 81.17. Patients with MSC injection had significantly higher Lysholm scores ( P = .007) and HSS scores ( P = .01) and higher proportions of ICRS grade 1 ( P = .03) and grade 2 ( P = .02) cartilage repair in the medial femoral condyle and grade 2 cartilage repair in the tibial plateau ( P = .04). There were no significant differences between groups in the IKDC score, KOOS Pain and Symptoms subscales, femorotibial angle, posterior tibial slope, or HKA angle. Conclusion: Intra-articular MSC injection may enhance the cartilage repair for patients who undergo HTO. However, evidence of improvement in knee functions remains limited. Registration: CRD42021291345 (PROSPERO).